Analisis Strategi Pemasaran Untuk Mengoptilmalkan Penjualan Sapu Lidi Dari Pelepah Sawit Dengan Menggunakan Metode Strengths, Weaknesses, Opportunities Dan Threats (SWOT) Di UMKM Mitra Bisnis - Fadil Iqbal; Wirda Novarika; Mahrani Arfa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out the strategies used to increase sales of broom sticks from palm fronds based on the SWOT method. To find out what indicators were studied in the research on marketing strategies for broom sticks from palm fronds using the SWOT method. This research uses a quantitative method where in When data collection is carried out using the Quantitative method, a questionnaire will be distributed containing indicators related to the SWOT method. Meanwhile, in data processing, data analysis will be carried out using quantitative methods, namely in the form of calculating the weight of the values ​​obtained in the questionnaire distributed to the marketing department in the MSME Business Partners. From the results of data processing, it was found that the Internal Factor Analysis Summary (IFAS) of strength and weakness factors had a score of 2.99 and the External Factor Analysis Summary (EFAS) above obtained a score of 2.79. From the matrix above, it is known that IFAS is in cell II and EFAS is in cell IV, which means that the strategy will refer to growth or development.